PEMANFAATAN MEDIA CHROMEBOOK PADA PEMBELAJARAN IPAS KURIKULUM MERDEKA DI SEKOLAH DASAR - Sumarni R Djaafar; Nasriani; Hasia Marto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the utilization of Chromebook media in thelearning of Natural and Social Sciences (IPAS) within the Merdeka Curriculum atState Elementary School 3 Karamat. This study employed a qualitative researchmethod, with two class teachers serving as the subjects. Data collection wasconducted through interviews, observation, and documentation. The resultsindicate that the utilization of Chromebooks in IPAS learning has been well-implemented, aligning with the indicators for the science and social aspects, aswell as process skills. Teachers have effectively used Chromebooks to deliversubject matter, access digital learning resources, and facilitate interactive learningactivities. Although the utilization is considered good, several inhibiting factorswere identified. These include the limited availability of Chromebook devices,inadequate internet access, and a lack of sufficient training for teachers regardingthe optimal use of Chromebooks.